Correlation of urban and rural settlements with Shigella sp. resistance pattern isolated from Bedadung River in Jember, Indonesia - Aryasatya, Dimas Widyadhana Bhanu; Agustina, Dini; Jauhani, Muhammad Afiful; Suswati, Enny (Universitas Gadjah Mada, 2025)
Purpose: This study aims to determine a correlation between settlement location and resistance patterns of Shigella sp. isolated from the Bedadung River in Jember, Indonesia. Method: The research method used was analytic observational with a cross-sectional design. Data analysis was performed using the Chi-Square test and, if not qualified, the Fisher exact test. Samples were obtained through a total sampling technique with a total sample size of 24. Results: Most samples were resistant to the antibiotic, and there was no relationship between residential location and resistance patterns of Shigella sp. isolated from Bedadung River, Jember Regency (p-value > 0.05). Conclusions: In conclusion, no significant relationship exists between the residential area and the resistance pattern of Shigella sp. isolated from Bedadung River, Jember Regency. Shigella sp. bacterial contamination is mainly found in Bedadung River water isolates in rural and urban areas. Shigella sp. bacteria found in rural and urban areas in the Bedadung River in Jember Regency have the same number.